2018
DOI: 10.1007/s12975-018-0655-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel Scaffolds: Towards Restitution of Ischemic Stroke-Injured Brain

Abstract: Chronic brain injury following cerebral ischemia is a severe debilitating neurological condition, where clinical intervention is well known to decrease morbidity and mortality. Despite the development of several therapeutic strategies, clinical outcome in the majority of patients could be better improved, since many still face life-long neurological deficits. Among the several strategic options that are currently being pursued, tissue engineering provides much promise for neural tissue salvage and regeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 201 publications
0
27
0
Order By: Relevance
“…Alternatively, hiPSC-derived cells can be grown as 2D and 3D cultures (brain organoids) that can be used for drug screening or in vitro disease modeling. (Khaing et al, 2014;George and Steinberg, 2015;Boisserand et al, 2016;Nih et al, 2016;González-Nieto et al, 2018;Gopalakrishnan et al, 2019). This is a strategy that has been largely unexplored in the context of TBI treatment but that could have extensive benefits.…”
Section: Tissue Engineering Strategiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Alternatively, hiPSC-derived cells can be grown as 2D and 3D cultures (brain organoids) that can be used for drug screening or in vitro disease modeling. (Khaing et al, 2014;George and Steinberg, 2015;Boisserand et al, 2016;Nih et al, 2016;González-Nieto et al, 2018;Gopalakrishnan et al, 2019). This is a strategy that has been largely unexplored in the context of TBI treatment but that could have extensive benefits.…”
Section: Tissue Engineering Strategiesmentioning
confidence: 99%
“…For instance, high molecular weight hyaluronic acid has been shown to decrease microglial inflammatory signaling (Austin et al, 2012). In addition to physical supports, biomaterials can provide trophic support by acting as a depot for soluble factors either delivered with the biomaterial (Wang et al, 2012;Cook et al, 2017;Nih et al, 2018) or secreted by infiltrating cells, thereby maintaining a high concentration of those factors where they are most needed (Pakulska et al, 2012;Khaing et al, 2014;George and Steinberg, 2015;Boisserand et al, 2016;Nih et al, 2016Nih et al, , 2018González-Nieto et al, 2018;Gopalakrishnan et al, 2019). In general, biomaterials have garnered significant interest as drug delivery vehicles, for their abilities to provide local, controlled release of a therapeutic over time.…”
Section: Tissue Engineering Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The difficulty of implementation of primary neuroprotection is the limited length of the therapeutic window, which cannot go beyond 5-6 h after damage. On the other hand, approaches aimed at enhancing brain plasticity, i.e., those considering effects on the damaged brain independent on the pharmacologic therapeutic window, such as stem cell or extracellular vesicle transplantation (Bang and Kim, 2019;Borlongan, 2019), or scaffold transplantation (Gopalakrishnan et al, 2019) have shown high therapeutic efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Injectable hydrogels can be used for the local delivery of drugs and have been widely used for the treatment of brain diseases (TBI and stroke) due to their good biocompatibility, biofunctionality, and ability to form via an in situ gelling process (21,22). The hydrogels themselves can be used as carriers to load various drugs, and the drug utilization e ciency can be improved while prolonging the action time of the drug by injecting it in situ or directly on the tissue surface (20).…”
Section: Introductionmentioning
confidence: 99%